THE IMPACT OF ONLINE REVIEWS AND RATINGS ON GENERATION Z'S TRUST IN SHOPEE IN PANCUR, BATU, DELI, SERDANG, NORTH SUMATRA - Rivaldi Sihombing; Syahfrida Hafni Sahir (RADJA PUBLIKA, 2025)
This study aims to determine the effect of Online Customer Review and Online Customer Rating on Customer Trust in Generation Z users of the Shopee application in Pancur Batu District, Deli Serdang. This study focuses on understanding how reviews and ratings given by Shopee users online can shape the level of consumer trust in the platform. The study uses a quantitative approach with a causal associative type to measure the cause-and-effect relationship between independent and dependent variables. The population in this study was Generation Z who actively use Shopee in Pancur Batu District with a total of 1,405 people. The sample was taken using a purposive sampling technique and calculated using the Slovin formula, so that 94 respondents met the criteria. The data collection technique was carried out by distributing questionnaires designed using a Likert scale. Validity and reliability tests showed that all instrument items used were valid and reliable. Data analysis was carried out using multiple linear regression with the help of SPSS version 25, as well as through classical assumption testing to ensure model suitability. The results of the study showed that Online Customer Reviews had a positive and significant effect on Customer Trust. Online Customer Rating was also proven to have a positive and significant effect on Customer Trust. Simultaneously, both variables together have a positive and significant influence on consumer trust in the Shopee platform. This result confirms that online reviews and ratings are important factors in building customer trust, especially among Generation Z.